KARAKTERISTIK DAN PERILAKU MERPATI TINGGI LOKAL JANTAN DAN BETINA - Mohamad Haekal Mahesa Kadri; Dian Septinova; Rr. Riyanti (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to 1) describe the qualitative characteristics of high pigeon (the coat color, head shape, tail shape, body shape, eye shape, the shape of the wings, beak shape and the shape of the foot at the local high pigeon male and female); 2) describe the behavior of pigeons move higher (fly, hanging, running, fighting), and mating behavior (male approaches the female, browse, and making out). This research are conducted in August 2015 in the Rawa subur Road No. 49, Enggal Centre Tanjung Karang, Bandar Lampung. This study used a descriptive exploratory conduct direct observation of the behavior of pigeons and doves characteristics of male and female local high. The results showed qualitative characteristics pigeons local high male and female varied: head shape (type round, type jenong, and type turtledove), beak shape (type rambon and type taper), shape (type of banana bod and ball type), the type of hair (tenuous and short) and the frequency and timing of moving the highest relative to the local high pigeon is flying, while the mating behavior is investigate. Key words: Characteristics, Behavior, Local High Pigeon Males and Females